Students’ Reflection in the Virtual Classroom - Adhikari, Khadak Raj (Academic Journal of Mathematics Education, 2022)
The main objective of this research was to increase the students’ interaction and find the effectiveness of online class from the students’ perspectives. The action research methodology has been applied during Covid-19 period when the mode of instruction was fully virtual. A survey was conducted at the end of the year to find the perception of students towards online classes. The sample consists of 83 students of grade 9 from Kaski district who had been studying mathematics by virtual mode. The main problem was that there was very little interaction between the teacher and the students in the virtual classroom and interest of students was very low towards learning mathematics. Upon regular treatment for a couple of months, students began to show the sign of interaction by asking many more questions as well as sharing their problems with the teachers and participated in each and every activity in the virtual class. To the end 45.8% of students responded that the online class was effective and beneficial for them.